Demand for Social Interest Housing and Effectiveness of Incentives for Family Subsidy Policy in Bogotá from 2000 to 2012 - Bolívar Silva, Carol Alejandra; Galindo León, Pedro Elías (Cooperativismo & Desarrollo, 2015)
Introduction: The policy for Social Interest Housing (vis from its Spanish acronym) has been designed to contribute towards improvement of the quality of life of families of limited means through the provision of a cash subsidy, according to the different socioeconomic conditions. Methodology: In Bogotá, the following indicators are taken into account: coefficient of use of the housing subsidy, interest rates for financing housing in real value, uvr, mortgage credit approval indicator, variation in the index of prices of new and used housing, demand for non-vis housing and employment rate. The objective is to determine the behavior of the Demand for Social Interest Housing (demvis) and the effectiveness of the incentives of the policy. Results: This research article summarizes the results found during comparison of the conceptual, theoretical and regulatory structure of the Social Interest Housing policy through a qualitative analysis that apparently shows the effectiveness of that policy and the fulfillment of the requirements with the aim of favoring families of limited means. Conclusions: Based on the econometric model, it can be seen that the housing subsidy has little effect on the dynamism of the demand for Social Interest Housing.
Keywords: interest; policy; social; subsidy; housing.